Stochastic ground motion simulation with geological site effects in damage asessment - Estêvão, João Manuel Carvalho (1998)
Damage assessment of structures with a mechanical non linear model demands the representation of seismic action in terms of an accelerogram (dynamic analysis) or a response spectrum (pushover analysis). Stochastic ground motion simulation is largely used in regions where seismic strong-motion records are available in insufficient number. In this work we present a variation of the stochastic finite-fault method with dynamic corner frequency that includes the geological site effects. The method was implemented in a computer program named SIMULSIS that generate time series (accelerograms) and response spectra. The program was tested with the MW= 7.3 Landers earthquake (June 28, 1992) and managed to reproduce its effects. In the present work we used it to reproduce the effects of the 1980’s Azores earthquake (January 1, 1980) in several islands, with different possible local site conditions. In those places, the response spectra are presented and compared with the buildings damage observed.